The Research of Sevim Ak's Stories in Terms of Suitability for Child Principle - Karaca, Gülay; Temizyürek, Fahri (Bartın Üniversitesi, 2017)
The purpose of this study is to research Sevim Ak's stories in terms of suitability for children principle. In accordance with this purpose, the suitability of thirty four stories in five books of Sevim Ak, with the inclusion seventeen stories in three story books published by Can Publishing and the seventeen stories in two story books published by Yapı Kredi Publishing, were researched in terms of suitability for children principle. In this study, the stories of Sevim Ak were researched within the consideration of the child's developmental characteristics and “the suitability to the child” principle under the following titles: 1. The necessary content features of Sevim Ak's stories in terms of suitability to the child: Subject, theme, character(s), language and expression, message and environment. 2. The necessary design features of Sevim Ak's stories in terms of suitability to the child: Paper, page layout and illustrations. While these titles are determined, the evaluation was carried out by scanning the body of literature by dwelling on how the suitability for children principle should be handled. While this evaluation was carried out, it was benefited from the study of Çakır (2013) titled of ''The Research of Stories in Turkish Coursebook İn Terms of The Suitability To The Child Principle”.

Bu çalışmanın amacı, Sevim Ak'ın öykülerini çocuğa görelik ilkesi açısından incelemektir. Bu amaç doğrultusunda Sevim Ak'ın Can Yayınları'ndan çıkan üç öykü kitabındaki on yedi öyküsü ve Yapı Kredi Yayınları'ndan çıkan iki öykü kitabındaki on yedi öyküsü olmak üzere,  beş öykü kitabındaki otuz dört öykünün çocuğa görelik ilkesine uygunluğu incelenmiştir. Bu çalışmada Sevim Ak'ın öyküleri, çocuğun gelişim özellikleri ve “çocuğa görelik” ilkesi dikkate alınarak şu başlıklar altında incelenmiştir: 1.       Sevim Ak'ın öykülerinin çocuğa görelikler açısından taşıması gereken içerik özellikleri: Konu,  tema  (izlek), karakter(ler), dil ve anlatım, ileti ve çevre. 2.       Sevim Ak'ın öykülerinin çocuğa görelikler açısından taşıması gereken tasarım özellikleri: Kâğıt,  sayfa düzeni ve resimlemeler. Bu başlıklar belirlenirken alanyazını taranarak çocuğa görelik ilkesinin nasıl ele alınması gerektiği üzerinde durularak buna göre değerlendirme yapılmıştır. Bu değerlendirme yapılırken Çakır (2013)'ın ''Türkçe Ders Kitaplarındaki Öykülerin Çocuğa Görelik İlkesi Açısından İncelenmesi'' adlı çalışmasından yararlanılmıştır.
Sevim Ak'ın Öykülerinin Çocuğa Görelik İlkesi Açısından İncelenmesi